2016
DOI: 10.1080/16070658.2016.1248062
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in the elderly residing in long-term care facilities: a cross sectional survey using the Mini Nutritional Assessment (MNA®) screening tool

Abstract: Objectives:The objective of this study was to determine and compare the nutritional status of the elderly in two long-term care facilities -one situated in a higher socio-economic area and one in a lower socio-economic area. Design: A cross-sectional study was undertaken. Setting: The study setting comprised two urban areas of Bloemfontein, Free State province, South Africa. Subjects: Sixty-two elderly residing in a long-term care facility from both the higher and lower socio-economic areas agreed to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…However, Alphas et al realised that more females (28%) were malnourished compared with men (17%). Moreover, similar to our findings, another cross-sectional survey in South Africa found a prevalence of 11.3% of malnutrition among older persons [ 48 ]. This higher prevalence of malnutrition may increase mortality and morbidity among the older person population in SSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, Alphas et al realised that more females (28%) were malnourished compared with men (17%). Moreover, similar to our findings, another cross-sectional survey in South Africa found a prevalence of 11.3% of malnutrition among older persons [ 48 ]. This higher prevalence of malnutrition may increase mortality and morbidity among the older person population in SSA.…”
Section: Discussionsupporting
confidence: 91%
“…This study summarises evidence on the factors influencing malnutrition in older persons in SSA (Table 1 ). Seventeen studies reported on the various factors associated with malnutrition; four studies revealed the association between socio-economic status and malnutrition [ 30 , 45 , 48 , 55 ], whereas seven studies were on dietary habits ([ 5 , 15 , 19 , 30 , 38 , 48 , 55 ]). Also, four studies showed a significant association between educational status and malnutrition [ 5 , 44 , 45 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Malnutrition is as an important factor for predicting morbidity and mortality among older persons [4]. Poor nutritional status in older people increases the risk of infections, disease period, poor wound healing, hospitalization rate, postoperative complications [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a cross-sectional survey in South Africa reported that a signi cantly higher percentage of participants from the lower socioeconomic area were found to be at risk of undernutrition than those from the higher socio-economic area (74.2% vs. 37.1%) [95% CI 19.8%; 51.4%]. Participants from the higher socio-economic area consumed signi cantly more uid and protein-rich foods than their counterparts (40).…”
Section: Discussionmentioning
confidence: 99%